Periglacial water paths within a rock glacier-dominated catchment in the Stepanek area, Central Andes, Mendoza, Argentina - Trombotto, Dario Tomas; Sileo, Noelia Romina; Dapeña, Cristina (Permafrost and Periglacial Processes)
In the region of the Stepanek rock glacier (69°19′/69°26′W, 32°55′/32°59′S), in the Province of Mendoza, Argentina, seasonal hydrochemical monitoring was carried out between 2013 and 2017. This paper describes underground and surface water flow, and their hydrochemistry, and provides an overview of how groundwater interacts with the rock glacier. The cryogenic basin of the study area where the hydrological flows originate has a surface area of 11.5 km2. The Stepanek rock glacier fills the valley and its permafrost influences water flow. Isotopic analyses of surface ephemeral streams and groundwater were made. Characteristic, naturally occurring δ2H and δ18O signatures of these samples indicate strongly that they are fed from within permafrost from the rock glacier, in response to the degradation of permafrost and melting of ground ice. Elevated values of Ni2+, Cd2+ and Zn2+ were detected in the meltwater runoff. Due to lithological factors, the Andean periglacial environment may indicate altitudinal differences in the hydrogeochemical results. Our hydrogeochemical research allows the interpretation of different water flows, directly observed or indirectly deduced, which cross the rock glacier. The new information allows for the development of a new conceptual rock glacier model that includes different flow paths. It is expected that this will become more important due to ongoing climate change. Fil: Trombotto, Dario Tomas. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Sileo, Noelia Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia ...